How Do Protected Areas Contribute to Human Well-Being? Multiple Mechanisms Perceived by Stakeholders in Chile - Llanos-Ascencio, J; Zorondo-Rodriguez, F; Rodriguez-Gomez, G (Springer, 2024)
Biodiversity conservation in designated protected areas reshapes the ways in which people interact with their ecosystems and each other, providing changes in their opportunities to satisfy different aspects of their well-being. The pathways linking human well-being and protected areas could be understood as one or more causal mechanisms that can be structured through nature’s contributions to people (NCPs), i.e., ecosystem services. We conducted semi-structured interviews with stakeholders in four Chilean protected areas to identify the multiple mechanisms through which protected areas contribute to human well-being. The stakeholders cited diverse NCPs from protected areas, including material, nonmaterial, and regulating ecosystem services. The stakeholders’ narratives suggested that protected areas satisfy several dimensions of human well-being, which varied both in frequency of citation across the protected areas and according to the stakeholders’ areas of interest. Protected areas were described as contributing to several dimensions of human well-being beyond economic benefits. The narratives indicated a set of multiple mechanisms linking ecosystem services provided by protected areas and satisfaction of dimensions of human well-being at the local level. We emphasize the need to design adaptive management plans for protected areas based on multiple mechanisms linking biodiversity protection and human well-being. Additionally, our results could facilitate the alignment of biodiversity conservation and community development agendas. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.